Desulfurization of JP-8 jet fuel: challenges and adsorptive materials. Issue 13 (14th February 2018) - Tran, Dat T.; Palomino, Jessica M.; Oliver, Scott R. J.
Abstract : This review describes ongoing efforts to remove the bulky organosulfur compounds from Jet Propellant 8 (JP-8) that cannot be removed by hydrodesulfurization. Abstract : The desulfurization of JP-8 (Jet Propellant 8) fuel is of interest to the U.S. military because of its potential use as a fuel source for solid oxide fuel cells (SOFCs). SOFCs can be used to supply a steady stream of power during military silent watch missions. Adsorptive desulfurization is a promising alternative to hydrodesulfurization, which is unable to remove refractory sulfur compounds and achieve the ultra-low sulfur levels necessary to prevent poisoning of SOFCs. Adsorptive desulfurization could be a portable, on-site process performed on JP-8 stocks already in the field. Within the vast field of fuel processing/reformation, herein we focus on the current status of adsorptive desulfurization performed on JP-8 jet fuel. Currently, the best performing sorbents are those utilizing high surface area porous frameworks with pore sizes large enough to accommodate sulfur contaminants. Additionally, a variety of metals in ionic, metallic, and oxide form serve as promising active sites within these sorbents. Most reports focus on reformation technologies and sorbent materials for gas-phase desulfurization and hydrogen purification of low-sulfur content diesel or light fraction jet fuel. JP-8 is unique to the Army in terms of supply. This review will thus focus on ongoing efforts in the room temperature liquid desulfurization of JP-8 and its higher levels of impurities that are more complex and difficult to remove.